Creación de un nuevo modelo de negocio denominado mini mall para ciudadelas o urbanizaciones que se encuentran alejada del perímetro urbano - Calle Castillo, Verónica Del Rocío (2010)
The project is the creation of a Mini Mall inside a house in a private area outside the city limits within which it does not appear in any grocery store, the house will have two plants in which to create nine rental locations for Merchants wishing to establish their businesses in the Mini Mall, so that on the ground floor will be 5 local and General Administration and upstairs 4 stores, also will be taken a place to implement the business of Mini Market. Mini Mall that will provide basic services and will provide home delivery for both traders and to potential customers. It will keep the right of admission to the establishment of trade potential, the house selected for the Mini Mall not suffer external adjustments to meet the regulations of urbanization.